2014
DOI: 10.1371/journal.pone.0102634
|View full text |Cite
|
Sign up to set email alerts
|

Influenza-Like-Illness and Clinically Diagnosed Flu: Disease Burden, Costs and Quality of Life for Patients Seeking Ambulatory Care or No Professional Care at All

Abstract: This is one of the first studies to (1) describe the out-of-hospital burden of influenza-like-illness (ILI) and clinically diagnosed flu, also for patients not seeking professional medical care, (2) assess influential background characteristics, and (3) formally compare the burden of ILI in patients with and without a clinical diagnosis of flu. A general population sample with recent ILI experience was recruited during the 2011–2012 influenza season in Belgium. Half of the 2250 respondents sought professional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 22 publications
2
59
0
1
Order By: Relevance
“…In addition to medically attended influenza, there will be a large number of influenza patients who never seek medical care. A Belgian study found that around half of those experiencing influenza‐like illness seeks medical counselling . Simulation studies from the pandemic in Norway support this finding, as an estimated 30% of the population was infected with the pandemic influenza virus, while less than 5% of the population consulted a doctor .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to medically attended influenza, there will be a large number of influenza patients who never seek medical care. A Belgian study found that around half of those experiencing influenza‐like illness seeks medical counselling . Simulation studies from the pandemic in Norway support this finding, as an estimated 30% of the population was infected with the pandemic influenza virus, while less than 5% of the population consulted a doctor .…”
Section: Discussionmentioning
confidence: 99%
“…A Belgian study found that around half of those experiencing influenza-like illness seeks medical counselling. 45 Simulation studies from the pandemic in Norway support this finding, as an estimated 30% of the population was infected with the pandemic influenza virus, while less than 5% of the population consulted a doctor. 46 Considering this, the impact on society caused by influenza infections is higher than observed in our study.…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…In the USA, medical costs totaled US$3,990 in 2012 for inpatients and US$730 for emergency department patients 7. In Belgium, the average direct medical cost per case in 2014 was €51–53 8. From a societal viewpoint, the total average mean cost for physician-diagnosed influenza and ILI at primary care level in Germany in 2015 was €514 for adults and €105 for children 9.…”
Section: Introductionmentioning
confidence: 99%
“…17 Children with influenza were more likely to report pain with breathing, headache, fatigue, arthralgias, and myalgias, whereas adults with influenza were more likely to report pain with breathing, vomiting, and arthralgias. Pleuritic chest pain, although not universally reported in ILI, has previously been described in patients with pandemic H1N1.…”
Section: Discussionmentioning
confidence: 93%